Area-based reviews and their aftermath: moving to a post-incorporation model for further education in England?. (2nd July 2020) - Spours, Ken; Hodgson, Ann; Grainger, Paul; Smith, David
ABSTRACT: This article draws on research into the further education (FE) Area-Based Review (ABR) process in London, England over the period 2016–2018 to suggest that the significance of ABRs can be judged as to the extent they reinforce or challenge the historical marketised model of FE. The implications of ABR are viewed historically through the conceptual lens of two governance continua – market/public (economic) and centralised/devolved (political). The research, involving repeated interviews with a range of FE social partners over a three-year period, developed the concept of two inter-related logics – a dominant 'Logic A' focused on FE college viability and merger and a subordinate 'Logic B' focused on regional skills strategies and greater collaboration between social partners. The significance of ABRs is assessed in relation to the wider English policy contexts that point to a need for greater skills coordination. At the same time, a comparison of ABRs in England with the 'regionalisation' of FE colleges in the other three countries of the UK highlights its relatively unplanned character. The article concludes with a discussion around the evolving relationship between the two Logics and argues that, albeit hesitantly, FE colleges in England may be moving towards a 'Post-Incorporation' phase.